Proposal for an Alliance Between Healthcare and Legal Area Professionals for Shared Public Health and Preventive Strategies in Italy and Europe - Claudio Costantino; Walter Mazzucco; Vincenzo Restivo; Ida Iolanda Mura; Gaetano Maria Fara; Giuseppe Giammanco; Sabrina Vecchio Verderame; Giuseppe Alessio Messano; Carmelo Massimo Maida; Alessandra Casuccio; Francesco Vitale (Frontiers Media S.A., 2020)
Following the implementation of the new Italian legislation on responsibility of healthcare workers, a multi-professional framework, involving representatives of the Italian public health professionals and legal professionals expert in the field, drafted a proposal of the actionable recommendations to be implemented in the management of civil and penal disputes arising from the practice of public health interventions. In order to prevent legal disputes concerning some public health fields such as vaccinations, cancer screening, environmental health surveillance, and hospital management, it should be primary taken into account to update guidelines in supporting decision-making processes, in accordance with the "best scientific evidence available." Furthermore, a multidisciplinary alliance between public health and legal area professionals should be encouraged and should be promoted both at national and European level.